Why Some Muslims Engaged in Violence: A Militarised Mentality - Ilyas Mohammed (Journal of Contemporary Governance and Public Policy, 2021)
Since 9/11 countering different types of violence through CVE and PVE programs have become a central policy concern for many in the Western and non-Western countries such as the UK, France, the United States and Indonesia. These countries have launched various CVE and PVE programs to prevent what scholars call radicalisation and de-radicalise those dammed to have been radicalised. These programs' focus is often to build community resilience and persuade individuals to adopt a liberal or state-oriented understanding of Islam. However, how successful these programs are is not clear. In some cases, these programs have been counterproductive because they have fostered Islamophobia and mistrust, as is the case with the UK's Prevent strategy. This paper will take the UK as a case study and propose a non-religious conceptual framework by using strain and fusion theory and interview data to explain why some British Muslims decided to engage in terrorism. In doing so, the paper will argue that if the UK government is to prevent such decisions, it needs to focus on addressing the socio-political causes that engender motivations to engage in terrorism.